2019
DOI: 10.1002/1438-390x.12001
|View full text |Cite
|
Sign up to set email alerts
|

Far from the madding crowd: Tolerance toward human disturbance shapes distribution and connectivity patterns of closely related Martes spp.

Abstract: To assess niche overlap between the most similar European sympatric carnivores, the pine marten Martes martes and stone marten Martes foina, and outline their potential distributions and connectivity corridors in Central Italy, we applied a multivariate kernel density procedure which allowed to assess both species' ecological hypervolumes based on a set of 16 environmental predictors and used the resulting probability of occurrence map as a resistance surface in electrical circuit theorybased models. Distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 86 publications
5
20
1
2
Order By: Relevance
“…The presence of both coniferous plantation and broadleaf and mixed forests influenced species occupancy positively. Our results expand upon previous habitat suitability studies (Balestrieri et al, 2018;Zub et al, 2018) (Caryl et al, 2012). These results may be particular to regions which are currently undergoing afforestation schemes driven by Government forestry bodies and timber production as in Ireland and Britain (Mitchell, 2000).…”
Section: Habitat Suitabilitysupporting
confidence: 86%
“…The presence of both coniferous plantation and broadleaf and mixed forests influenced species occupancy positively. Our results expand upon previous habitat suitability studies (Balestrieri et al, 2018;Zub et al, 2018) (Caryl et al, 2012). These results may be particular to regions which are currently undergoing afforestation schemes driven by Government forestry bodies and timber production as in Ireland and Britain (Mitchell, 2000).…”
Section: Habitat Suitabilitysupporting
confidence: 86%
“…Despite their historical decline being driven by persecution, there has been little research into how to minimize future human-wildlife conflict. Existing research on small carnivore conservation in Europe typically focuses on large-scale modelling of occurrence (Balestrieri et al 2019, Zub et al 2018, with limited fine-scale examination of populations and how fulfilling biological requirements in modern human modified environments may affect their recovery.…”
mentioning
confidence: 99%
“…The European pine marten Martes martes is a small carnivore currently recovering in Britain and Ireland following severe historical decline driven by habitat loss and persecution (Langley and Yalden 1977, O'Mahony et al 2017, Sainsbury et al 2019. Recent research demonstrates the species may be limited by human disturbance to the more remote, forested parts of Europe (Balestrieri et al 2019, Twining et al 2020. There is some evidence that it is the structural elements of ancient forest that are required, not the presence of old-growth forest per se (Brainerd et al 1995, Caryl et al 2012.…”
mentioning
confidence: 99%
“…Habitat use by the stone marten is considered to be driven by competition with the pine marten (Martes martes), which should be able to outcompete the stone marten in forested habitats (Delibes 1983). More recently, it has been suggested that the strictly nocturnal stone marten may be more tolerant of human disturbance than the cathemeral pine marten, and thus may manage better than the latter in rural habitats (Balestrieri et al 2019). Nonetheless, in the Iberian Peninsula, southwards of the southern edge of pine marten distribution, the stone marten is a mainly forest-dwelling species, which selects low human density areas (Virgós and Casanovas 1998).…”
Section: Introductionmentioning
confidence: 99%